End Use Promotion of Micro Hydro Project for its Sustainable Development (A Case Study of Malagad Khola MHP) - Dhakal, Rajesh; Poudel, Laxman (Journal of the Institute of Engineering, 2018)
This research is an attempt to explore the sustainability of a Micro-hydro power project. A micro-hydropower project can make a substantial impact in developing countries where significant water resources exist and where economically viable alternatives are few, such as Nepal. This research explores the opportunities to sustain a micro-hydropower project for a long period with acceptable revenues. Willingness to pay among the community and possibility of productive end uses have been studied. The study finds many possible end uses that can improve sustainability of the project. Journal of the Institute of Engineering, 2017, 13(1): 125-132